Effect of Antihipertensive Drugs And Banana (Musa Sp.) To Potassium Serum Levels of Hypertensive Wistar Rats Model - Zora Olivia; Arinda Lironika Suryana (Journal of Agromedicine and Medical Sciences, 2018)
Consumption of antihypertensive drugs has the potential to cause drug and food interactions. Captopril/lisinopril can increase potassium levels by inhibiting the activity of renin angiotensin aldosterone. If captopril/lisinopril is consumed together with bananas, there is a risk of hyperkalemia because bananas are a high pottasium fruits. The aimed of this study was to determined the effect of captopril/lisinopril given with banana (Musa Sp) on potassium serum levels of Rattus novergicus strain Wistar hypertension model. This research was an experimental study with a randomized post-test control group design.Thirty (30) male wistar strain rats aged 2-3 months, weighing 200-250 grams were divided into 6 groups. The control group (K-) non-hypertensive rats, the control group (K+) hypertension rats+standard diet, the treatment group (P1) hypertension rats + standard diet + captopril 2.25 mg/kgBB, the treatment group (P2) hypertensive rats + standard diet + lisinopril 0.6 mg/kgBB, treatment group (P3) hypertension rats + standard diet + captopril with banana and treatment group (P4) hypertension rats + standard diet + lisinopril with bananas. Measurement of potassium serum levels was carried out using electrolyte analyzer. Furthermore, the data were analyzed by One Way ANOVA test. The results showed that there were no significant differences in potassium serum levels between all groups. In conclusion, both of captopril 2.25 mg/kgBB and lisinopril 0.6 mg/kgBB given together with banana 9g/kgBB for 3 days hasn’t caused drug and food interactions. Keywords: banana fruits, captopril, lisinopril, potassium serum